Deskripsi Faktor-faktor Pernikahan Dini pada WUS di Kecamatan Bandungan, Kabupaten Semarang Tahun 2017 - Nurnahariah Nurnahariah; Djoko Nugroho; Atik Mawarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Bandungan is a districts with the highest early marriage case in Semarang Regency at 2017. From 463 married couples, as many as 23.75% of women and 46% of men were married early. Based on medical and psychological considerations, women are ideally married between 20-25 years old and 25-30 years old for men. This age is considered to be the most appropriate for married because they are mature. The purpose of the study was to describe the knowledge, customs, environment of residence and early marriage at WUS. Type of this research is descriptive with a cross sectional study design. The population was all women who were officially married in Bandungan District in 2017 that is 259 people. The sampling technique uses simple random sampling with a sample 74 people. Data were analyzed by univariate. The results showed that respondents had good knowledge (56.8%) with mostly correct answers from respondents to the early marriage questions for women affecting women's emotional stability (95.9%), customs with the highest percentage not supporting (63.5%) with the respondent answering no for question habit of the villagers wed children after having their maturation sign (94.6%) and WUS who practiced early marriage (51.4%), the living environment with the highest percentage that is unreachable (63.5%) with the most answer no for question often communicate with the owner of karaoke (93.2). There needs to be an increase in knowledge of WUS who conduct early marriage and the socialization by KUA employees so that early marriage can be reduced.